PENGARUH KEPERIBADIAN DAN PEMBERDAYAAN TERHADAP KINERJA KARYAWAN PT.ASTRA INTERNATIONAL Tbk-DAIHATSU MEDAN - Hermawan Fauzi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The purpose of this study was to find out and analyze the Influence of Personality and Empowerment on Employee Performance at PT.Astra International Daihatsu Tbk.The research method used is exploratory research, where the variable is measured by a Likert scale. The method of data collection is done by interview (interview), with a list of questions (questionnaire) and study documentation. The population in this study were 65 PT. Astra International Daihatsu Tbk employees. Sampling using the Jenu sample method. In this study the population is relatively small, which is as many as 65 people. Data processing uses SPSS version 23 software, with descriptive analysis and hypothesis testing of multiple regression analysis.The results of the study show that: (1) partially the Personality variables affect the Performance of PT. Astra International Daihatsu Tbk; (2) the Empowerment variable partially affects the Employee Performance of PT. Astra International Daihatsu Tbk; (3) simultaneously there is a positive and significant influence between the variables of Personality and Empowerment on Employee Performance of PT.Astra International Daihatsu Tbk